Current Trends in the Treatment of Pediatric Hydrocephalus: A Narrative Review Centered on the Indications, Safety, Efficacy, and Long-Term Outcomes of Available Treatment Modalities - Dimitrios Panagopoulos; Georgios Stranjalis; Maro Gavra; Efstathios Boviatsis; Stefanos Korfias; Ploutarchos Karydakis (MDPI AG, 2024)
The pathophysiologic substrate of pediatric hydrocephalus has not been thoroughly elucidated. Valve-based shunt systems have constituted the main therapeutic option since the late 1950s. The initially used systems were concerning the ventricular system and the atrium. In the 1970s, VA shunts were not the main stay of treatment as the preferred option for the terminal end of the drainage system was the peritoneum. Our review analyzes these valve types and attempts a comparison, based on their functional characteristics. Nowadays, the only available surgical alternative for the treatment of hydrocephalus is ETV. This technique is associated with lower infection rates as well as, on average, a lower re-operation rate. Another term that deserves special mention is related to the outcome of ETV in children who had a medical history of previously incorporated shunts and who were subsequently suffering from shunt malfunction. Well-recognized predictive factors associated with secondary ETV failure include age, early onset of hydrocephalus, and prematurity. Although several attempts have been made in order to establish the optimum surgical treatment management in the different subgroups of patientswho are suffering from shunt dysfunction, there is no universal agreement. Therefore, this review attempts to identify the specific subpopulations of patients in whom the insertion of a drainage system as the preferred treatment modality is associated with an optimum long-term prognosis, compared to ETV, and vice versa. The objective of our study is to analyze the safety, efficacy, and outcomes of drainage devices and ETV in pediatric hydrocephalus patients.